HRTEM characterization of gold nanoparticles produced by wheat biomass - Armendáriz, V. (2004)
In this study, the bio-reduction of Au(III) to Au(0) by wheat biomass and the subsequent production of gold nanoparticles of various shapes and sizes is presented. The dry biomass was ground and sieved in order to assure a uniform particle size and having more area of biomass exposed to the gold. Wheat biomass was exposed to a 0.3mM potassium tetrachloroaurate solution at pH values of 2, 3, 4, 5, and 6 for three and a half hours at room temperature. After that time, the biomass pellets were analyzed using a high resolution transmission electron microscope, JEOL-4000 EX, in order to characterize the gold nanoparticles. The results showed that wheat biomass produced nanostructures of the following morphologies: Fcc tetrahedral (T), decahedral (Dh), hexagonal (He), icosahedral multitwinned (I), irregular shape (Irr), and rod shape nanoparticles. The highest percent of the nanoparticles formed had a particle size ranging from 10-30 nm.